Pleasure dan Pain sebagai Landasan Pembentukan Kebijakan Hukum: Relevansi dan Kritik Terhadap Teori Utilitarianisme dalam Sistem Hukum Modern - Jupiter Henviean; Susanti S Tandung (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The concepts of pleasure and pain are two fundamental categories in the Utilitarian Theory developed by Jeremy Bentham. This study examines the role of these two categories as benchmarks of usefulness in the context of achieving legal objectives, which include justice, certainty and legal utility. From a Normative Juridical perspective, this study shows that pleasure and pain are not merely subjective experiences, but rather objective indicators of the utility of law in social life. Law will be deemed successful if it achieves its objectives by maximizing pleasure and minimizing pain in social life. Bentham's utilitarianism has been criticized for potentially ignoring distributive justice and minority rights. The thoughts of John Stuart Mill and Robert Nozick's critique of Libertarianism represent corrective efforts that enrich the ethical framework of utilitarianism. Mill's emphasis on the quality of happiness and Nozick's affirmation of individual rights emphasize the moral limits that need to be considered in applying the principle of usefulness.